Electrophysiological markers of cognitive control in the Stroop task: analysis of event-related potentials - Shlyakhov, Ivan Sergeevich; Gorbunov, Ivan Anatol'evich; Dakhnovskaya, Maria Sergeevna (Психолог, 2025)
Cognitive control plays a key role in regulating behavior and suppressing automated responses, especially in conditions of cognitive conflict. Its mechanisms allow for the suppression of stereotypical reactions and the direction of attention towards achieving set goals. Cognitive control is particularly important in situations where it is necessary to overcome interference between competing stimuli. This study focused on the neurophysiological markers of conflict information processing. To achieve the research objectives, the electroencephalography (EEG) method was employed. The classical Stroop task was used as the experimental paradigm, which models situations of cognitive conflict. As a result, this research analyzed event-related potentials (ERPs) in the Stroop task to study the neurophysiological mechanisms of conflict information processing. The experiment involved 36 participants, whose ERPs were analyzed to identify the following components: N2 (conflict monitoring), N400 (interference suppression), and the late positive component (LPC), associated with conflict resolution. The results showed that the N2 component demonstrated a significant increase in amplitude under conflict stimuli, confirming its association with activation of the anterior cingulate cortex (ACC) in conflict detection. The N400 component appeared as a pronounced negative wave in centro-parietal regions, indicating its involvement in suppression mechanisms. LPC, in turn, showed higher amplitude during conflict resolution, indicating the mobilization of cognitive resources for task control. Thus, the obtained data supports the theory of two-phase cognitive control, where the early phase (N2) is responsible for conflict detection, the middle phase (N400) is related to interference suppression, and the late phase (LPC) reflects conscious information processing and adaptation. This research complements existing data on the neurophysiological bases of cognitive control and opens avenues for further investigation of individual differences and the influence of external factors on the effectiveness of conflict information processing.